Impulse flow dependency of galanin release in vivo in the rat ventral hippocampus. - Consolo, S (1994)
Using microdialysis and a sensitive RIA, we have studied the in vivo release of the neuropeptide galanin (GAL) from the ventral hippocampus of freely moving rats. The spontaneous outflow of GAL-like immunoreactivity (GAL-LI) (1.8 +/- 0.3 fmol per ml per 20 min) was dependent on the presence of extracellular Ca2+ and was inhibited by tetrodotoxin. Evoked release induced by infusion of KCl (60 mM) or veratridine (148 microM) was also Ca(2+)-dependent and sensitive to tetrodotoxin. Electrical stimulation of the ventral limb of the diagonal band nuclei induced a frequency-dependent (50-200 Hz) and tetrodotoxin-sensitive overflow of GAL-LI in the hippocampus. In vitro GAL-LI release (1.0 +/- 0.02 fmol per ml per 5 min), studied in slices of rat ventral hippocampus, was also Ca(2+)-dependent and was increased in a concentration-dependent manner by KCl depolarization. This study demonstrates the release of the neuropeptide GAL in the rat central nervous system. The in vivo release is related to the activity of the cholinergic GAL-LI-containing cells in the septal diagonal band nuclei. The results are discussed in relation to the coexistence of GAL and acetylcholine within the septal/diagonal band complex.